Jesus the Christ - The Only Way to God and to Human Flourishing - Thangaraj, Melchizedec Thomas (Journal of ecumenical studies, 2017)
The article discusses the elaboration of Jesus the Christ on the Christian affirmation in the settings of interfaith dialogue and understanding. It examines the influence of several factors to the reinterpretation or rejection of religious traditions including historical, theological, ecclesiological, psychological, and epistemological. It also cites the historical experience of people with different faiths.